THE ROLE OF SAIDA ZUNNUNOVA IN UZBEK LITERATURE AND HER DESCRIPTION OF WOMEN CHARACTERS - Daminova Kumush Rustam qizi, (KONFERENSIYALAR, 2025)
Annotation.  Saida  Zunnunova  is  one  of  the  prominent  figures  of  20th-century  Uzbek literature, whose works deeply explore the portrayal of women. As a poet and writer, she vividly captures the inner world of women and the social, spiritual, and psychological struggles they face. Zunnunova  does  not  depict  women  merely  in  traditional  roles  but  as  strong,  independent individuals who possess the ability to define their own destinies and withstand life's challenges. In her works, women often overcome life's hardships through their inner strength and perseverance. The poet portrays women through lyrical, realistic, and symbolic means, highlighting their dreams, love, devotion, and personal growth. In Zunnunova’s stories, female characters are shown as active participants in social life, striving for personal transformation and growth. Zunnunova’s literary legacy  plays  a  significant  role  not  only  in  Uzbek  literature  but  also  in  the  development  and enhancement of female representation in literature. She portrays women not just in their traditional family roles but as modern and socially active individuals. Her works emphasize the true role, inner strength, and independence of women, contributing a unique and invaluable perspective to Uzbek literature.